2021
DOI: 10.33225/pec/21.79.912
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Academic Flow in Students' Achievement and Well-Being

Abstract: Flow experience is related to well-being. Still, the question arises as to whether the flow is beneficial because of its intensity and frequency, or its contribution to well-being depends on the domain in which it is experienced. It was hypothesized that flow experienced in a domain that is perceived important and useful (i.e., the academic domain) contributes more to students’ well-being than flow experienced in domains that are perceived as less important and less useful (leisure and routine activities) even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The experience of flow is also associated with student well-being, as many studies conducted on non-Chinese populations have also confirmed. From the perspective of university education, it seems essential that students have the opportunity to experience flow in their studies, as it is a pleasurable state associated with better performance and overall well-being (Olcar et al, 2021). In Chinese culture, conscientiousness is seen as a value.…”
Section: Discussionmentioning
confidence: 99%
“…The experience of flow is also associated with student well-being, as many studies conducted on non-Chinese populations have also confirmed. From the perspective of university education, it seems essential that students have the opportunity to experience flow in their studies, as it is a pleasurable state associated with better performance and overall well-being (Olcar et al, 2021). In Chinese culture, conscientiousness is seen as a value.…”
Section: Discussionmentioning
confidence: 99%
“…Exploratory factor analysis confirmed the single-factor structure of the scale. Previous research showed adequate convergent and discriminative validity (Pavot & Diener, 1993) as well as reliability of the scale (Olčar et al, 2021).…”
Section: The Present Studymentioning
confidence: 93%
“…The condition in which a person shows the power of concentration when carrying out an activity, accompanied by inner motivation, and a sense of comfort in participating in an activity is called flow [1,2]. In the field of education, the condition of flow where students carry out activities related to academic activities such as following the entire learning process, both in learning and doing assignments is called academic flow [3,4]. At present, where the impact of the Covid 19 pandemic is still being felt, the teaching and learning process is experiencing different conditions from the conditions of the previous teaching and learning process.…”
Section: Introductionmentioning
confidence: 99%